2008
DOI: 10.1021/la8005234
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nanomechanical Properties in the Tribological Performance of Phospholipid Biomimetic Surfaces

Abstract: The role of phospholipid bilayers in controlling and reducing frictional forces between biological surfaces is investigated by three complementary experiments: friction forces are measured using a homemade tribometer, mechanical resistance to indentation is measured by AFM, and lipid bilayer degradation is controlled in situ during friction testing using fluorescence microscopy. DPPC lipid bilayers in the solid phase generate friction coefficients as low as 0.002 (comparable to that found for cartilage) that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
82
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 50 publications
10
82
1
Order By: Relevance
“…Earlier findings on lubricated sliding between hydrated surface layers including hydrated ions [3][4][5] , surfactants [6][7][8] , polymers [10][11][12] or liposomes 9 could not reveal the underlying process. This is because the measured friction was a convolution of the hydration lubrication with other dissipation pathways, such as the activated processes described above, or deformation [6][7][8][9] or entanglement [10][11][12] effects in the boundary layers themselves.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Earlier findings on lubricated sliding between hydrated surface layers including hydrated ions [3][4][5] , surfactants [6][7][8] , polymers [10][11][12] or liposomes 9 could not reveal the underlying process. This is because the measured friction was a convolution of the hydration lubrication with other dissipation pathways, such as the activated processes described above, or deformation [6][7][8][9] or entanglement [10][11][12] effects in the boundary layers themselves.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the measured friction was a convolution of the hydration lubrication with other dissipation pathways, such as the activated processes described above, or deformation [6][7][8][9] or entanglement [10][11][12] effects in the boundary layers themselves. The present study elucidates this-for the simplest case of trapped, hydrated ions-by unravelling this convolution and separating the dissipation modes (and in future work it would be interesting to examine different aspects such as the case of different ions and of the transition between the regimes).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, several reports have described very low friction forces between phospholipid bilayers up to high pressures. 11,37,49,50 Perhaps counterintuitively, it was found that DPPC bilayers in the fluid state have a higher load bearing capacity than such layers in the frozen state. 37 This is illustrated in Fig.…”
Section: Amphiphilic Moleculesmentioning
confidence: 97%